A novel prototype 3/5 laparoscopic needle driver: A validation study with conventional laparoscopic needle driver - Arvind P Ganpule; Chaitanya S Deshmukh; Tanmay Joshi (Journal of Minimal Access Surgery, 2018)
Introduction: The challenges in laparoscopic suturing include need to expertise to suture. Laparoscopic needle holder is a” key” instrument to accomplish this arduous task. Instrument: The objective of this new invention was to develop a laparoscopic needle holder which would be adapted to avoid any wobble (with a shaft diameter same as a 5mm port), ensure accurate and dexterous suturing not just in adult patients but pediatric patients alike (with a short shaft diameter) and finally ensure seamless throw of knots with a narrow tip configuration. Validation: We did an initial evaluation to evaluate the validity of the prototype needle holder and its impact on laparoscopic suturing skills by experienced laparoscopic surgeons and novice laparoscopic Surgeons. Both the groups of surgeons performed two tasks. The first task was to grasp the needle and position it in an angle deemed ideal for suturing. The second task was to pass suture through two fixed points and make a single square knot. At the end of the tasks each participant was asked to complete a 5- point Likert's scale questionnaire (8 items; 4 items of handling and 4 items of suturing) rating each needle holder. In expert group, the mean time to complete task 1 was shorter with prototype 3/5 laparoscopic needle holder (11.8 sec Vs 20.8 sec). The mean time to complete task 2 was also shorter with prototype 3/5 laparoscopic needle holder (103.2 sec Vs 153.2 sec). In novice group, mean time to complete both the task was shorter with prototype 3/5 laparoscopic needle holder. Conclusion: The expert laparoscopic surgeons as well as novice laparoscopic surgeons performed laparoscopic suturing faster and with more ease while using the prototype 3/5 laparoscopic needle holder.